2021
DOI: 10.1007/s11102-021-01136-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects and clinic reflections of the COVID-19 outbreak in patients with acromegaly and Cushing’s disease

Abstract: Purpose Patients with acromegaly and Cushing's disease (CD) may experience significant problems related to the COVID-19 outbreak. We aimed to investigate the psychosocial effects of the pandemic and reveal the follow-up characteristics. Methods The single center, cross-sectional, web-based survey study included patients with acromegaly and CD, PCR-confirmed COVID-19 patients and healthy volunteers without known any chronic disease. The semi-structured sociodemographic data form, The State-Trait Anxiety Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies, parents of children with physical illness reported a medium-sized increase in psychological distress from prior to during the COVID-19 pandemic (13,16,19,20,34). This deterioration in the mental health of parents has pervasive sequelae, negatively affecting their well-being (59), and also the health and well-being of their children (60)(61)(62). Psychological distress has been shown to hinder caregiving responsibilities, which can result in poorer health outcomes for children with physical illness (63-65), many of which have complex care needs that may be compounded in the Data are presented as regression coefficient (standard error).…”
Section: Summary Of Findingssupporting
confidence: 84%
“…Consistent with previous studies, parents of children with physical illness reported a medium-sized increase in psychological distress from prior to during the COVID-19 pandemic (13,16,19,20,34). This deterioration in the mental health of parents has pervasive sequelae, negatively affecting their well-being (59), and also the health and well-being of their children (60)(61)(62). Psychological distress has been shown to hinder caregiving responsibilities, which can result in poorer health outcomes for children with physical illness (63-65), many of which have complex care needs that may be compounded in the Data are presented as regression coefficient (standard error).…”
Section: Summary Of Findingssupporting
confidence: 84%
“…Prevalence of post-traumatic stress disorder was not different in patients with acromegaly vs. Cushing disease vs. healthy controls but higher in SARS-CoV-2 patients; however, frequency of abnormal trait anxiety was significantly higher in patients with acromegaly and SARS-CoV-2 patients vs. those with Cushing disease and healthy controls. Finally, treatment discontinuation rate was higher in acromegaly patients vs. those with Cushing disease [107].…”
Section: Acromegalymentioning
confidence: 87%
“…In another single-centre, cross-sectional, web-based survey psychosocial status of patients with acromegaly and Cushing disease was compared to that of SARS-CoV-2 infected patients and healthy volunteers [107]. Prevalence of post-traumatic stress disorder was not different in patients with acromegaly vs. Cushing disease vs. healthy controls but higher in SARS-CoV-2 patients; however, frequency of abnormal trait anxiety was significantly higher in patients with acromegaly and SARS-CoV-2 patients vs. those with Cushing disease and healthy controls.…”
Section: Acromegalymentioning
confidence: 99%
“…Our results on the psychosocial condition of participants may have been modulated when not aggravated during the COVID pandemic, when the study took place. This could be related to the lack of usual followup due to con nement requirements, as reported by different authors [27][28][29]. Thus, we cannot rule out that the con nement caused by the COVID-19 pandemic during the second outbreak in our geographical area may have potentially contributed to an increase in the state of anxiety in acromegalic patients, although we believe that this exceptional situation does not devaluate the results obtained.…”
Section: Discussionmentioning
confidence: 66%